Upaya Peningkatan Motivasi Anak Menggunakan Media Promosi Video Interaktif di Panti Asuhan Lima Bintang Helvetia Medan - Kirana Patrolina Sihombing; Irma Syafriani Sinaga (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
The high cases of dental and oral disease were still caused by the behavior of people who are not aware of the importance of maintaining healthy teeth and mouth. The purpose of this community dedication was to provide knowledge to children so that they are selective in choosing snacks, both those that are healthy for teeth and those that damage teeth, to improve parenting in implementing clean and healthy living behaviors, especially how to brush teeth properly and correctly. The method of implementation was pre-test and post-test, counseling through interactive video playback for 30 children from the Lima Bintang Helvetia orphanage, Medan. In this activity, a good and correct way of brushing your teeth is demonstrated by using a dental phantom as well as demonstrations of examples of foods that are healthy for your teeth, as well as the practice of brushing your teeth together and the correct way to chew fruit. Based on the results of the examination after the community service activities, students' knowledge increased 53% was good, the parenting form of the children has a clean and healthy lifestyle by brushing their teeth properly and correctly 2 times a day (in the morning after breakfast and at night before going to bed) with a duration of 2 minutes of brushing. In addition, children already understand snack foods, both those that are healthy for teeth and those that are detrimental to teeth.